Motor activity Log-Brazil: Reliability and relationships with motor impairments in individuals with chronic stroke Motor activity Log-Brasil: Confiabilidade e relações com a função motora em indivíduos com acidente vascular cerebral crônico - Pereira N.D.* (2012)
The Motor Activity Log (MAL) assesses the spontaneous use of the most affected upper limb with the amount of use (AOU) and quality of movement (QOM) scales during daily activities in real environments in individuals with chronic stroke. Objectives: This study translated the testing manual into Portuguese and assessed the inter-rater and test-retest reliabilities of the MAL, based upon the Brazilian manual version. Methods: The inter-rater reliability was evaluated by comparing the results of two examiners, and the test-retest reliability was tested by comparing the results of two evaluations, repeated one-week apart with 30 individuals with chronic hemiparesis (55.8±15.1 years). Results: The intra-class correlation coefficients (ICCs) for the total scores were adequate for both the inter-rater (0.98 for the AOU and 0.91 for QOM) and test-retest reliabilities (0.99 for both scales). Conclusions: The results suggested that the MAL was reliable to evaluate the spontaneous use of the most affected upper limb after stroke.